A disciplina de história da educação em perspectiva histórica : da Faculdade de Filosofia, Ciências e Letras à Universidade Federal do Espírito Santo (1951-2000) - Oliveira, Sandro Nandolpho de (2014)
The research analyzes the historical development of the discipline “History of Education”, taught at the Sciences Philosophy and Letters Faculty of The Espírito Santo, subsequently incorporated to the Federal University of Espírito Santo, between the years of 1951 and 2000. It investigates the historical constitution of the discipline, the pragmatics, legal and institutional transformations related to the History of Education” discipline, as well the historiographical approaches, periodization and time concepts, history and education. The theoric and methodologic fundamentation articulates itself dialogically from the conceptual and methodologic constructions of Carlos Ginzburg and Mikhail Bakhtin. The voices and the dialogs, printed in the discipline and its guideline’s narratives (in the superficial or deep layers that were found in the consulted and analyzed documental corpus, that respond to: educational programs, transparencies, laws, curriculum, department documents, reviews and book reports, compulsory and complementary bibliography, valuations and interviews) were investigated from the polyphony and dialogism concept, common to both. Sought to reassemble a complex historical, and not a directly perceptible reality, apparently insignificant data, in the documental corpus – clues, evidences and signs -. While investigating historically the trajectory of the discipline "History of Education" and its teaching, (from the legal, pragmatics and institutionals parameters) was possible to see that the deeper changes operated in the discipline don’t originate from legislation and curricular restructuring, but from places of production and socialization of historical knowledge. During the reporting period, the two historiographical production spheres that most influenced the approaches, periodization and concepts of time, history and education of the discipline of “History of Education” in the researched Pedagogy course, were: the editor responsible for the publication and disclosure of the Manuais de História da Educação da coleção Atualidades Pedagógicas (1951-1979) e os Programas de Pós-graduação em Educação e História (1980 - 2000). Between 1951 and the late 1970’s the influence of Manuais de História da Educação is observed in the organization and programming of the teaching of “History of Education” and an philosophical approach toward the history of pedagogical ideas and analysis of philosophers and educators thoughts about education and its inserts in European philosophical doctrines. Since 1980, the economical, political and ideological approaches of the historical educative contexts began to predominate in the educational programs in the disciplines of “History of Education I and II” and remained until mid 1990. In the discipline of History of Education I, the approach is marked by analysis of production and organization contexts of social classes; with respect to the discipline of History of Education II, until mid 1995, dealing with Brazilian education. Since the approach grounded in the Teoria da Dependência after 1995, the consulted documents begin to show other brands that suggests an approach toward the political and social dimension, addressing the history of Brazilian education, from the social movements and its educational projects.